Handbook of Psychology 2003
DOI: 10.1002/0471264385.wei0712
|View full text |Cite
|
Sign up to set email alerts
|

Gender Issues in the Classroom

Abstract: Koch reviews the literature on gender socialization of students as they participate in the social and academic culture of the classroom. Research on classroom practices and policies that foster gender stereotypes and limit opportunity for females and males is followed by research on curriculum, classroom interaction, and school climates that promote gender equity. Information is presented on the importance of increasing educators' awareness of their gender expectations and how hidden curriculum and gender‐diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 13 publications
0
19
0
Order By: Relevance
“…Boys are considered to be biologically disposed to more assertive, energetic, and aggressive behavior than girls, and therefore, they would be expected to have more conflictual relationships with teachers (Carlson, Tamm, & Gaub, 1997;Zahn-Waxler, Shirtcliff, & Marceau, 2008). According to gender socialization theory, gendertypical behaviors and attitudes are reinforced in students through differential treatment of boys and girls (for review see Koch, 2003). Teachers tend to be more tolerant of dominant and autonomous behaviors in boys, whereas they respond more favorably to calm and submissive behaviors in girls (Basow, 2004;Meece & Scantlebury, 2006).…”
Section: Theoretical Notions About Gender Differencesmentioning
confidence: 99%
“…Boys are considered to be biologically disposed to more assertive, energetic, and aggressive behavior than girls, and therefore, they would be expected to have more conflictual relationships with teachers (Carlson, Tamm, & Gaub, 1997;Zahn-Waxler, Shirtcliff, & Marceau, 2008). According to gender socialization theory, gendertypical behaviors and attitudes are reinforced in students through differential treatment of boys and girls (for review see Koch, 2003). Teachers tend to be more tolerant of dominant and autonomous behaviors in boys, whereas they respond more favorably to calm and submissive behaviors in girls (Basow, 2004;Meece & Scantlebury, 2006).…”
Section: Theoretical Notions About Gender Differencesmentioning
confidence: 99%
“…Research has shown that for STEM subject areas girls learn best in environments that promote collaborative learning, hands-on experiences, creativity, and practical applications (AAUW, 2000; Campbell et al, 2002;Kafai, 1998;Koch, 2002;Wenglinksy, 2000). Given that girls' interest in STEM careers is impacted by their interest in STEM subject areas (Sadler et al, 2012), it is important to distinguish specific skills and activities in K-12 education that help to cultivate girls' interest in STEM subject areas.…”
Section: Related Literaturementioning
confidence: 99%
“…Previous studies conducted in school settings in western societies have suggested that teachers and peers have significant roles in children’s gender socialization experiences (Duffy et al 2001; Fromberg 2005; Koch 2003; Morgan 2001). Interestingly, Fagot et al (1985) found that teachers’ differential attention and responses toward common behaviors in American toddlers preceded the emergence of any gender differences in toddlers’ behaviors that were measured.…”
Section: Introductionmentioning
confidence: 99%